Enzyme action as bearing on the validity of the ionic-dissociation hypothesis and on the phenomena of vital change - Armstrong, Henry E. (1904)
In discussing the changes which attend fermentation, I pointed out, in 1895, that “Such changes are known to occur entirely within the cell and are presumably functions of the protoplasm; in other words, they probably occur within very complex molecular systems of extreme instability, perhaps under the influence of, in contact with, the very same hydrolyst (enzyme) which is so active, when separated from the cell, in promoting the hydrolysis of cane sugar; or if not, of substances of a similar nature.” This explanation has gained greatly in prob ability now that it is established that the sucroclastic enzymes are very closely related to the alcoholic ferments.